Magnetic resonance imaging of the entorhinal cortex and hippocampus in mild cognitive impairment and Alzheimer's disease. Issue 4 (1st October 2001) - Du, A T; Schuff, N; Amend, D; Laakso, M P; Hsu, Y Y; Jagust, W J; Yaffe, K; Kramer, J H; Reed, B; Norman, D; Chui, H C; Weiner, M W
Abstract : OBJECTIVES: To explore volume changes of the entorhinal cortex (ERC) and hippocampus in mild cognitive impairment (MCI) and Alzheimer's disease (AD) compared with normal cognition (NC); to determine the powers of the ERC and the hippocampus for discrimination between these groups. METHODS: This study included 40 subjects with NC, 36 patients with MCI, and 29 patients with AD. Volumes of the ERC and hippocampus were manually measured based on coronal T1 weighted MR images. Global cerebral changes were assessed using semiautomatic image segmentation. RESULTS: Both ERC and hippocampal volumes were reduced in MCI (ERC 13%, hippocampus 11%, p<0.05) and AD (ERC 39%, hippocampus 27%, p<0.01) compared with NC. Furthermore, AD showed greater volume losses in the ERC than in the hippocampus (p<0.01). In addition, AD and MCI also had cortical grey matter loss (p< 0.01) and ventricular enlargement (p<0.01) when compared with NC. There was a significant correlation between ERC and hippocampal volumes in MCI and AD (both p<0.001), but not in NC. Using ERC and hippocampus together improved discrimination between AD and CN but did not improve discrimination between MCI and NC. The ERC was better than the hippocampus for distinguishing MCI from AD. In addition, loss of cortical grey matter significantly contributed to the hippocampus for discriminating MCI and AD from NC. CONCLUSIONS: Volume reductions in the ERC and hippocampus may be early signs of AD pathology that can be measured using MRI.